The Views of An Nur Student Islamic Boarding School Students on the Difference in the Determination of the Beginning of the Months of Ramadan, Syawwal, and Dzulhijjah - Ahmad Akhyar Tsabit; Tsabit; Dimas Nafiko (Cv. Kayaswara, Indonesia, 2025)
This research aims to understand the perspectives of students (santri) at Pesma An-Nur Islamic Boarding School, Surabaya, regarding the differences in determining the beginning of the Hijri months particularly Ramadan, Shawwal, and Dhu al-Hijjah. Every year, Muslims in Indonesia often face disagreements about when to start fasting or celebrate Islamic holidays due to the use of different methods, such as rukyat (moon sighting) and hisab (astronomical calculations). Islamic organizations like Nahdlatul Ulama (NU), Muhammadiyah, and the Indonesian government follow varying approaches, which often leads to differences in worship schedules. This study uses a survey method through an online questionnaire (Google Form) distributed to students of Pesma An-Nur, who come from various regions and organizational backgrounds. The collected data was analyzed to identify their understanding of moon sighting methods, their affiliation with specific Islamic organizations, and their attitudes toward the ongoing differences in determining the start of the Hijri months. The results show that most students tend to follow the government's decision to maintain unity and avoid confusion during important religious events. Many are more familiar with the rukyat method, and some have even participated in moon sighting activities themselves. Even though opinions differ, most students adopt a tolerant attitude and see these differences as part of Islamic diversity rather than a source of conflict. They believe mutual respect and understanding are key to preserving religious harmony in society.